In vitro and in situ effects of atorvastatin and ezetimibe on P-glycoprotein expression and function (Bangladesh Journal of Pharmacology, 2016)
P-glycoprotein (P-gp) is a membrane transporter responsible for the active efflux from the cell. Inhibition of the activity may lead to clinically significant drug-drug interactions. This study was performed to investigate the effects of atorvastatin and ezetimibe on the function and expression of P-gp. The in vitro rhodamine-123 (Rho123) efflux assay and Western blot in Caco-2 cells, and the in situ rat single-pass intestinal permeability model followed by high performance liquid chromatography were developed. Rho123 intracellular accumulation in 100 µM of atorvastatin- and ezetimibe-treated cells was significantly higher than that in control cells (p